Volume index is a risk factor for recurrence even in patients with clinical stage IA endometrial cancer undergoing either laparotomy or laparoscopy: A retrospective study - Kenro Chikazawa; Sachiho Netsu; Ken Imai; Azusa Kimura; Tomoyuki Kuwata; Ryo Konno (Wolters Kluwer Medknow Publications, 2022)
Objectives: The objective of the study was to investigate the long-term outcomes, in particular, recurrence risk, especially tumor volume, for Stage IA endometrial cancer and to identify the risk factors for recurrence. Materials and Methods: This single-center retrospective study analyzed women who underwent primary surgical treatment for the International Federation of Gynecology and Obstetrics Stage IA (Grade 1 or 2) endometrioid carcinoma at our institute between January 2010 and July 2018. Patients' demographic characteristics, including age, operative time, number of lymph nodes, final stage, volume index as tumor volume, and final histological type, were reviewed. A total of 168 patients were enrolled, with 95 and 73 patients in the laparotomy and laparoscopy groups, respectively. The Cox proportional hazards model was used to adjust for prognostic factors in the analysis including upstaged patients, tumor histology, lymphovascular invasion, and volume index. Results: There was no difference in the recurrence rate between laparoscopic and open surgeries for Stage IA endometrial cancer. The operative time was longer, and the amount of blood loss was lesser in the laparoscopy group than in the laparotomy group. For all patients undergoing either laparoscopy or open surgery, upstaged ≥IB, nonendometrioid Grade 1 or 2, lymphovascular invasion, and volume index ≥36 were significant independent recurrence risk factors. Conclusion: Laparoscopic surgery for Stage IA endometrial cancer is technically and oncologically safe. Patients with a high-volume index have a higher recurrence risk. Furthermore, the volume index can be a recurrence predictor in low-risk endometrial cancer patients.